Effects of fiscal consolidation on income inequality: Narrative evidence from South America - Dante Cardoso; Laura Carvalho (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
Based on a narrative dataset constructed by David and Leigh (2018) that covers nine South American economies in the period 1982-2017, this paper estimates dynamic effects of fiscal consolidations on income inequality from Jordá (2005)'s local projections method. Results suggest that fiscal consolidations lead to a rise in income inequality in all specifications and data panels. When decomposing fiscal shocks, spending-based fiscal consolidations appear to significantly increase the Gini index, while tax-based fiscal consolidations do not show statistically significant effects on income inequality. The rise in the Gini index for disposable income caused by a spending-based fiscal adjustment of 1% of GDP varies between 1.74 and 3.22% in five years depending on the selected data panel (country-years). The magnitude of this effect is higher than in most of the previous studies carried out for OECD countries.
Keywords: D30; D63; E60; E62; 330; income inequality; fiscal consolidation; fiscal austerity; South America; local projections